2023
DOI: 10.1111/dme.15132
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the barriers and facilitators to dietary modification in people living with type 2 diabetes and pre‐diabetes from South Asian ethnic populations

Abstract: Aims: Lifestyle and dietary modification are effective in the prevention and management of Type 2 diabetes Mellitus (T2DM). However, South Asian (SA) populations living in Western countries have low adherence rates to healthcare advice and experience poor diabetes control and clinical outcomes compared with the general population. This systematic review aimed to summarise the barriers and facilitators of dietary modification within people from South Asian (SA) ethnicity with T2DM or pre-diabetes. Methods: A sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…34 On the other hand, transformative interventions should be culturally appropriate and offer palatespecific advice, retaining tradition, enjoyment, and family identity. 11 A key finding of this study found lay understandings of healthy eating do not generally conform to dietary guidelines, and health interventions. There were many mixed messages given to first and second generations by health professionals, about what is deemed 'healthy'.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…34 On the other hand, transformative interventions should be culturally appropriate and offer palatespecific advice, retaining tradition, enjoyment, and family identity. 11 A key finding of this study found lay understandings of healthy eating do not generally conform to dietary guidelines, and health interventions. There were many mixed messages given to first and second generations by health professionals, about what is deemed 'healthy'.…”
Section: Discussionmentioning
confidence: 80%
“…23 There was a lack of awareness about the nutritional components of eating foods which were high in sugar and fat across all generation groups, which meant people struggled to take measures to substitute their diets. 11 Early detection and understanding food and lifestyle are integral to prevent or delay complications and should continue to be a major public health campaign. 24 Similar to other studies in the UK, we found that traditional foods were deemed important in maintaining cultural roots across all generations; participants held beliefs that traditional foods were important to health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, promoting the incorporation of lentils into dietary traditional patterns may improve glycemic control amongst persons who may struggle with dietary advice for disease management that promotes the exclusion of many foods in their traditional diet (20). Indeed, competent care, including dietary advice that aligns with cultural practices, is important for self-management and treatment adherence (20,21).…”
Section: Introductionmentioning
confidence: 99%